2021
DOI: 10.3390/pr9101835
|View full text |Cite
|
Sign up to set email alerts
|

Wet Torrefaction of Poultry Litter in a Pilot Unit: A Numerical Assessment of the Process Parameters

Abstract: A numerical model for the wet torrefaction of poultry litter in a pilot unit was developed in this study. The model accounted for the following process steps: preheating biomass in a feed hopper, feeding biomass into the reactor, fluidized-bed generation using superheated steam, and the supply of additional heat by the electric heating of the reactor walls. Following a “black box” approach, a major assumption of the model is that the behavior of the fluidized-bed reactor is similar to a completely stirred tank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The yields of non-condensable gases obtained from the innovative WT process have already been reported in previous studies [24,25].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The yields of non-condensable gases obtained from the innovative WT process have already been reported in previous studies [24,25].…”
Section: Introductionmentioning
confidence: 64%
“…The side walls of the reactor were heated electrically to maintain the required temperature in the reactor. A detailed description of the operation of the pilot reactor for WT has been provided in [25].…”
Section: Experimental Setup and Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Ayub et al (2022) developed the simulation model of hydrothermal gasification for syngas production from poultry litter waste using Aspen Plus software and suggested that this process is economic-environmentally friendly and energy-saving compared with direct landfilling disposal, and the results indicated that the model has a better yield of hydrogen and methane gas with superior lower heating value at 540 • C, 25 MPa, and 20% feedstock concentration [54]. Isemin et al (2021) developed a numerical model for the wet torrefaction of poultry litter waste and successfully estimated the optimal duration required for the completion of this process under different conditions of temperature, batch weight, reactor dimensions, etc., and showed that the wet torrefaction of poultry litter increased the carbon content by 17% and reduced the oxygen content 2.46-fold while raising the heat of combustion by 12.5% [55].…”
Section: Modeling and Simulations Of Poultry Waste Treatment Processesmentioning
confidence: 99%